Assessment of orofacial functions in children using 'off track' mobile application: A cross-sectional study - Prajakta P Patwardhan; Amar N Katre (Journal of Dental Problems and Solutions - Peertechz Publications, 2023)
Introduction: Orofacial dysfunctions interfere with normal growth and development and may lead to multiple outcomes, including malocclusion. Assessment of Orofacial functions is thus critical in children. Methods: 'Off Track', a mobile-based app was used for orofacial functional assessment. The domains assessed were breathing, swallowing, chewing, speech, sleep, and others. The dysfunctions in each domain and the 'Off Track' score distribution were represented as frequency with percentages. Fisher's exact test was used to detect the difference between the age groups. Unadjusted odds were estimated to assess the association between feeding history and breathing dysfunction, feeding history and sleep dysfunction, and breathing dysfunction and sleep dysfunction. Result: The 'Off Track' scores 3, 4, 5, and 6 were recorded in 42.9%, 39.3%, 14.3% and 3.6% of the population, respectively. Most of the participants (89.29%) showed dysfunction in the breathing domain followed by swallowing (75%). The difference between the age groups was not significant (p > 0.05). Odd's ratios estimated for feeding history of the child and, mouth breathing and sleep dysfunction were not statistically significant. Conclusion: Orofacial dysfunctions are widely prevalent in children and 'Off Track' may serve as a chairside user-friendly app-based screening tool to assess orofacial functions in children.